Comparative functional analysis between human and mouse chitotriosidase: Substitution at amino acid 218 modulates the chitinolytic and transglycosylation activity - Kimura, Masahiro; Watanabe, Takashi; Sekine, Kazutaka; Ishizuka, Hitomi; Ikejiri, Aoi; Sakaguchi, Masayoshi; Kamaya, Minori; Yamanaka, Daisuke; Matoska, Vaclav; Bauer, Peter O; Oyama, Fumitaka (International journal of biological macromolecules, 2020)
Chitotriosidase (Chit1) and acidic mammalian chitinase (AMCase) have been attracting research interest due to their involvement in various pathological conditions such as Gaucher's disease and asthma, respectively. Both enzymes are highly expressed in mice, while the level of AMCase mRNA was low in human tissues. In addition, the chitinolytic activity of the recombinant human AMCase was significantly lower than that of the mouse counterpart. Here, we revealed a substantially higher chitinolytic and transglycosylation activity of human Chit1 against artificial and natural chitin substrates as compared to the mouse enzyme. We found that the substitution of leucine (L) by tryptophan (W) at position 218 markedly reduced both activities in human Chit1. Conversely, the L218W substitution in mouse Chit1 increased the activity of the enzyme. These results suggest that Chit1 may compensate for the low of AMCase activity in humans, while in mice, highly active AMCase may supplements low Chit1 activity.
Keywords: Chitin; Amino Acid Substitution; Humans; regulace genové exprese enzymů; Escherichia coli; hexosaminidasy; Chitinolytic activity; lidé; Recombinant Proteins; zvířata; myši; Transglycosylation; Hexosaminidases; Mice; rekombinantní proteiny; glykosylace; substituce aminokyselin; chitinasy; Gene Expression Regulation, Enzymologic; Animals; Chitinases; Glycosylation; Chitotriosidase; chitin